Towards guidance for the design and placement of vegetated filter strips - Duzant , Julia H. (Cranfield University, 2008)
A combined field, laboratory and modelling approach to the study of vegetated filter strips (VFSs) was carried out in order to provide guidance on optimum design and placement for trapping sediment from overland flow. Monitoring of fifteen established filter strips in the Parrett Catchment, England, informed on the complexity of intercepting flow pathways to optimise filter strip performance. Results suggest that a 6 m VFS will trap an average of 1.74 t year -1 of material from a field of 1 ha, but this is highly variable depending on design, placement and management factors. In most cases the majority of coarse sediment is trapped at the upslope edge of the VFS and is typically >85% sand. A revised Morgan-Morgan-Finney model was tested against a range of field and laboratory datasets and an efficiency coefficient of 0.7 was achieved. When testing the model against the field results from the Parrett Catchment, an active filter strip area was used. This took into account only the area of the filter strip effective in trapping sediment due to the convergence and bypassing of flow pathways. In the field, filter strip performance will be improved by reducing concentrated flow reaching the strip and ensuring that flow does not bypass the strip through burrows and gateways, using in field erosion control, maintaining level ground between the field and filter strip edge and managing the strip to maximise the density of vegetative material, particularly the number of vegetative stems. Potential applications for the research include a field based Decision Support System, design of filter strip biophysical architecture and catchment planning.